2013
DOI: 10.1002/ps.3579
|View full text |Cite
|
Sign up to set email alerts
|

Enhance knowledge on sustainable use of plant protection products within the framework of the Sustainable Use Directive

Abstract: The approach adopted, taking into account the variability in farm structure, cropping pattern, risk attitude and economic availability, is not an instrument to identify the most suitable protection strategy for a given crop in a given period, but to help professional users to improve their practices in managing PPPs on farms and to make the most appropriate choices leading to reduced environmental and human risk, without compromising the profitability of agricultural production and food standards. This work ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…Depending on the knowledge sources that farmers consult, their opinion of environmental protection and the negative consequences associated with the use of plant protection products are shaped differently [46]. In many cases, the farmers do not understand the risks associated with the use of plant protection products [47]. This is confirmed by the results of our research, in which farmers' awareness of crop disease is low.…”
Section: Discussionsupporting
confidence: 64%
“…Depending on the knowledge sources that farmers consult, their opinion of environmental protection and the negative consequences associated with the use of plant protection products are shaped differently [46]. In many cases, the farmers do not understand the risks associated with the use of plant protection products [47]. This is confirmed by the results of our research, in which farmers' awareness of crop disease is low.…”
Section: Discussionsupporting
confidence: 64%
“…It has been reported that poor knowledge regarding pesticide risks and handling among inhabitants of the Vehari District in Pakistan contributed to high exposure levels to organochlorine pesticides, particularly among farm workers [ 22 ]. As all stages in the use of pesticides on farms could generate risks for the operator and the environment, a basic recommendation is to promote training for pesticide users and adoption of good agronomic practices to improve sustainable use of pesticides [ 28 ]. To achieve sustainable use of pesticides, it is necessary that everyone is conscious about the risks to both human health and the environment associated with the use of plant protection products.…”
Section: Discussionmentioning
confidence: 99%
“…The lower adoption of IPM practices in Nepal could be attributed by several factors such as limited availability of insect monitoring and control options, lack of sufficient knowledge and confidence in non-chemical pest control measures, inadequate government pesticide regulation enforcement, and a large gap in information sharing between extension workers and farmers [21,[28][29][30][31]. Adoption of agricultural practices not only depends on a lack of awareness, but also other agronomic and local farm-related factors such as farm structure, cropping pattern, risk attitudes, and economic burden [35]. Extension agencies should consider these factors before making plans during launching any extension program [36].…”
Section: Concept Of Integrated Pest Management (Ipm)mentioning
confidence: 99%